Clinical characteristics and outcomes for patients with non‑metastatic castration-resistant prostate cancer - Peter Arnold (Nature Portfolio, 2021)
Abstract This study used linked, routinely-collected datasets to explore incidence, clinical characteristics and outcomes of prostate cancer (PC) patients who experience a rise in prostate-specific antigen (PSA) levels despite androgen deprivation therapy (ADT), without evidence of metastases in their patient record, termed non-metastatic castration-resistant PC (nmCRPC). Routinely collected administrative data in Wales were used to identify patients diagnosed with PC and nmCRPC from 2000–2015. Logrank tests and Cox proportional hazard models were used to compare time-to-events across subgroups defined by PSA doubling time and age. Of 38,021 patients identified with PC, 1,465 met nmCRPC criteria. PC incidence increased over the study period, while nmCRPC categorizations reduced. Median time from PC diagnosis to nmCRPC categorization was 3.07 years (95% confidence interval [CI] 2.91–3.26) and from nmCRPC categorization to metastases/death was 2.86 years (95% CI 2.67–3.09). Shorter PSA doubling time (≤ 10 months, versus > 10 months) was associated with reduced time to metastases or death (2.11 years [95% CI 1.92–2.30] versus 5.22 years [95% CI 4.87–5.51]). Age was not significantly associated with time to metastases/death. Our findings highlight key clinical characteristics and outcomes for patients with nmCRPC prior to the introduction of recently approved treatments.